Estimating the dietary and health impact of implementing mandatory front-of-package nutrient disclosures in the US: A policy scenario modeling analysis. - Nadia Flexner; Daniel Zaltz; Eva Greenthal; Aviva A Musicus; Mavra Ahmed; Mary R L'Abbe (PLoS ONE)
Background Recognized as a cost-effective policy to promote healthier diets, mandatory front-of-package labeling (FOPL) identifying foods high in sodium, sugar, and saturated fat has been adopted and implemented in ten countries, and is currently under consideration in several others including the US. However, its potential impact on dietary intake and health have not yet been estimated in the US context. Objectives To estimate (1) the potential dietary impact of implementing mandatory nutrient-specific 'high in' FOPL among US adults; and (2) the number of diet related non-communicable disease (NCD) deaths that could be averted or delayed due to estimated dietary changes. Methods Baseline and counterfactual dietary intakes of sodium, sugars, saturated fats, and calories were estimated among US adults (n = 7,572) using both available days of 24h recall data from the 2017-2020 National Health and Nutrition Examination Survey (NHANES). The National Cancer Institute method was used to estimate usual intakes and distributions, adjusting for age, sex, misreporting status, weekend/weekday, and sequence of recall. To estimate counterfactual dietary intakes, we modeled two reduction scenarios observed in experimental and observational studies that examined changes in sodium, sugars, saturated fat and calorie content of food and beverage purchases due to nutrient-specific 'high in' FOPL. This study used the Preventable Risk Integrated ModEl (PRIME) to estimate potential health impacts. Results Estimated mean dietary reductions of 156 mg and 259 mg/day of sodium, 10.1 g and 7.2 g/day of sugars, 1.08 g and 4.49 g/day of saturated fats, and 38 kcal and 57 kcal/day of calories were observed under the two policy scenarios tested. Between 96,926 (95% UI 89,011-105,284) and 137,261 (95% UI 125,534-148,719) diet related NCD deaths, primarily from cardiovascular diseases (74%), could potentially be averted or delayed by implementing mandatory nutrient-specific FOPL in the US. Overall, more lives would be saved in males than females. Conclusions Findings suggest that implementing mandatory nutrient-specific 'high in' FOPL in the US could significantly reduce sodium and total sugar intakes among US adults, resulting in a substantial number of NCD related deaths that could be averted or delayed. Our results can inform current food policy developments in the US regarding the adoption and implementation of FOPL regulations.